Феномен предательства как предмет обсуждения - Городяненко, В. (Социология: теория, методы, маркетинг, 2007)
The paper presents an attempt to comprehend the betrayal phenomenon, emphasizing the distinction between moral, legal, and sociological approaches to the problem. To reveal the treacherous behavior factors, the following question is raised: is it a norm of behavior or a state of mind? In conclusion, the author stresses that the betrayal phenomenon inhering in a society requires more careful study.